Description of the larva of Phyllopetalia apollo Selys and redescription of that of Hypopetalia pestilens Mclachlan (Anisoptera: Austropetalidae) - Pessacq, Pablo (2009)
The P. apollo larva is described for the first time and the larva of H. pestilens is redescribed.These are the first records of these spp. for Argentina and for the easternslope of the Andes. In order to determine the larval instars, length of inner wing padswas plotted against head width and a linear regression was estimated for both spp. 6instars were identified for H. pestilens and 8 for P. apollo.